Tinjauan Alur Prosedur Pelayanan Pasien Rawat Jalan Peserta BPJS (Studi Kasus Rumah Sakit Islam Ar-Rasyid Palembang Tahun 2021) - Aryani, Yuliza (JOURNAL OF HEALTH SCIENCE, 2024)
The purpose of this study was to determine the flow of procedures for outpatient services for BPJS participants at the Ar-Rasyid Islamic Hospital Palembang. This research method used a descriptive method with a qualitative approach. In the results of this study, the registration area consisted of 2 counters, the first counter for BPJS patient registration and the counter for BPJS patients second for general patient registration. The number of registration officers consists of 3 officers who are tasked with entering the identity of new patients and old patients into the computer database system and in charge of classifying medical record documents according to the clinic intended by the patient. The conclusion of this study is that the outpatient registration procedure for BPJS participants at the Islamic Hospital Ar-Rasyid Palembang is in accordance with the permanent procedure for registering outpatients. Keywords : Procedure Flow, Outpatient, BPJS